JOINT VENTURE: STRATEGY TO OBTAINTHE MANAGERIAL COMPETITIVENESS IN PERU - Maguiña F., Raúl (2004)
This article proposes a managerial competitiveness strategy using the Joint- Venture enterprise, rising out of alliances linking business units, by analizing its making-up process through legal and clear compromise requirements, framed within the peruvian law, and with the purpose of getting feasibility of various investment projects, in any production sector in our country.